2014
DOI: 10.1128/jcm.02297-13
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Hepatitis Delta Virus in Sub-Saharan Africa

Abstract: Hepatitis D virus (HDV) is a satellite of hepatitis B virus (HBV), and infection with this virus aggravates acute and chronic liver disease. While HBV seroprevalence is very high across sub-Saharan Africa, much less is known about HDV in the region. In this study, almost 2,300 blood serum samples from Burkina Faso (n ‫؍‬ 1,131), Nigeria (n ‫؍‬ 974), Chad (n ‫؍‬ 50), and the Central African Republic (n ‫؍‬ 118) were screened for HBV and HDV. Among 743 HBsAg-positive serum samples, 74 were positive for HDV antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
76
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(86 citation statements)
references
References 42 publications
7
76
2
Order By: Relevance
“…These results are comparable to some other studies in sub-Saharan Africa (SSA) done in similar settings [14][15][16] but quite different in other selected sub-populations including those with chronic liver disease in West Africa where a high anti-HDV prevalence ranging from 12.2 to 81.7% was documented 17 . Also other studies in Africa have showed varying prevalence rates of HDV ranging from 0-50% in different countries [18][19][20] .…”
Section: Discussionsupporting
confidence: 81%
“…These results are comparable to some other studies in sub-Saharan Africa (SSA) done in similar settings [14][15][16] but quite different in other selected sub-populations including those with chronic liver disease in West Africa where a high anti-HDV prevalence ranging from 12.2 to 81.7% was documented 17 . Also other studies in Africa have showed varying prevalence rates of HDV ranging from 0-50% in different countries [18][19][20] .…”
Section: Discussionsupporting
confidence: 81%
“…5,10 Phylogenetic analysis was performed in this study to evaluate further relatedness of the strains circulating in Australia. 33 In contrast, the genotype 1 African strains from Australian patients tended to originate from East Africa (Fig. 3) were born in either Liberia or Sierra Leone, located on the west coast of Africa.…”
Section: Discussionmentioning
confidence: 99%
“…In Mauritania a prevalence rate of 33.1% among HBsAg positive patients was recently reported, and HDV was associated with more aggressive disease than HBV infection alone (122). Other studies show wide differences in sero-prevalence in HBsAg positive liver patients, ranging from 1.3% in a Nigerian center, to 50% in Central African Republic and 66% in Gabon (123,124). However it should be kept in mind that data on anti-HDV seroprevalence are lacking from several African areas.…”
Section: The Case Of Low Endemicity Regionsmentioning
confidence: 95%